Multiple semantics of black and white in online fashion discourse (based on Сhanel fashion stories) - Lukianets, Halyna (My University, 2020)
The article presents multiple semantics of color terms black and white in Chanel online fashion discourse, including wide range of meanings, namely colorless, monochromatic, dark vs light, contextual and gray shades. Connection between color terms semantics and creation of brand image is established
Keywords: color terms; кольорові терміни; contextual meaning; контекстуальне значення; colorless; безбарвний; monochrome referential meaning; монохромне посилальне значення; кафедра іноземних мов професійного спрямування